Delving into the Impacts of Air Pollution on Sex, Health, Environment, and Pollution-related Policies in Nepal: A Scoping Review - Ritika Parajuli; Saurya Aryal; Sabin Khanal; Roshan Pudasaini; Nisam Sharma (Nepal Journal of Public Health, 2026)
Background: Air pollution poses a serious threat to public health as it contributes to a high prevalence of non-communicable diseases (NCDS) such as respiratory illness and cardiovascular diseases. This scoping review aimed to provide an overview of the impacts of air pollution on sex, health, and the environment, with a brief highlight on pollution-related policies in Nepal. It reviews the environmental effects of air pollution and existing policies for controlling air pollution. Methods: This review followed the five-stage methodological framework outlined by Arksey and O'Malley and was reported by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews. A comprehensive search was conducted across databases, including Frontiers, Google Scholar, and PubMed, using keywords related to air pollution, its impact, and policies. 104 were initially identified, with 12 meeting the inclusion criteria. Results: The review synthesizes the findings from studies conducted between 2018 and 2024, indicating that women, particularly involved in cooking with biomass fuels, face higher exposure to harmful pollutants, leading to serious health outcomes like chronic obstructive pulmonary disease (COPD), eye disorders, and adverse pregnancy outcomes. The studies revealed that the concentration of particulate matter (PM2.5) has often exceeded World Health Organization guidelines, and indoor and outdoor air pollution negatively impact environmental health and human wellbeing. Conclusion: The study underscores the urgent need for targeted interventions and policy measures to mitigate air pollution and protect vulnerable populations, particularly women, in Nepal. Further research is essential to address existing gaps for different sexes and inform effective public health strategies.